First observation of CP violation and improved measurement of the branching fraction and polarization of B0 -> D*+ D*- decays - Collaboration, B; Kronenbitter, B; Adachi, I; Aihara, H; Arinstein, K; Asner, D; Aushev, T; Aziz, T; Bakich, A; Barrett, M; Belous, K; Bhardwaj, V; et al. (2012)
We report the measurement of the branching fraction, the polarization, and the parameters of the time-dependent CP violation in B0 -> D*+ D*- decays using a data sample of 772 million BB pairs, collected at the Y(4S) resonance with the Belle detector at the KEKB asymmetric-energy e+e- collider. We obtain a branching fraction of B = (7.82 +- 0.38 +- 0.63) x10^{-4}, a CP-odd fraction of R_\perp = 0.138 +- 0.024 +- 0.006 and, additionally, a fraction of the longitudinal component in the transversity base of R_0 = 0.624 +- 0.029 +- 0.011. The measured values of the parameters of the CP violation are S_{D*+ D*-} = -0.79 +- 0.13 +- 0.03 and A_{D*+ D*-} = 0.15 +- 0.08 +- 0.04.